Jenis Frasa dalam Berita Kompas.com Rubrik Jagat Literasi Edisi Agustus – September 2025 - Anindiya Arvitadevi; Afiqah Dien Ramadhani; Ghiensza Kriska Jeconia; Dariel Ramadhan Sahari; Chelsea Fidela Maritza Siam; Asep Purwo Yudi Utomo; Rossi Galih Kesuma; Nabila Zata Yummi (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
This research examines the range of phrase types appearing in Kompas.com news articles published in the “Jagat Literasi” section during the August–September 2025 period. It seeks to identify and categorize various phrase structures, such as nominal, verbal, adjectival, prepositional, pronominal, numeral, and adverbial phrases, found within the selected articles. In addition to classification, the study provides a qualitative explanation of the structural characteristics, functions, and usage tendencies of the most frequently occurring phrase types in the corpus. Employing a qualitative research design, this study relies on textual data as its primary source, generating descriptive findings derived from careful observation and analysis of written materials. All identified phrases are interpreted and systematically described to offer a comprehensive understanding of how they function in digital news discourse. The findings highlight the dominance and distribution of several phrase categories and reveal patterns that characterize language use in literacy-themed journalism. Academically, this study contributes to syntactic research by offering a reference for further investigations on phrase usage in online media and by enabling comparative analysis across different platforms or sections. Practically, it enhances readers’ and students’ awareness of effective, precise, and stylistically appropriate language use, supporting improved writing practices aligned with established linguistic conventions.